Fundamentals for the positive development of the child - Miguel Díaz, Mario de (Pulso. Revista de educación, 2013)
After the adaptation phase of university degrees to the process of European convergence and overcome since the first years of the new era, we find a high rate of rejection of the new curricu¬lum, questioning its timeliness and consistency. The aim of this study was to analyze some of the factors that have constrained the process of adaptation of new Degrees in the two key is¬sues that were considered to promote European Higher Education: curriculum renewal and meth¬odological innovation. Our work pretending to be a critical look at how you have managed this pro¬cess by identifying some of the weaknesses of the university system that have helped institutions from having effectively taken advantage of the op¬portunities offered by the regulatory framework necessary to effect reform.
Keywords: Renewal of University Degrees; Curriculum Reform; Methodological Innovation; Adaptation to the RHEA; European Convergence Process